Building Financial Resilience of Boarding House Employees Through Financial Literacy (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Inflation and post-COVID-19 economic uncertainty have placed significant financial pressure on low-income workers, including boarding house employees. This study aims to analyze the effects of financial literacy, financial attitude, and economic pressure on personal financial management behavior and financial resilience among boarding house employees in Semarang Regency. A mixed-methods sequential explanatory approach was employed, with the quantitative phase (n=150) analyzed using PLS-SEM, followed by a qualitative phase (n=15) using thematic analysis. Results indicate that financial literacy (β=0.312; p